(untitled) (Annals of Medical Research, 2022)
Aim: This study aimed to determine preoperative echocardiographic predictors of postoperative atrial fibrillation (POAF) in patients undergoing beating-heart coronary artery bypass grafting (CABG) surgery. Materials and Methods: 84 patients undergoing off-pump isolated CABG were prospectively enrolled. The left atrium area (LAA) was measured from the apical four-chamber projection at the end-ventricular systole, and then indexed to BSA for the left atrial area index (LAAI). POAF was detected with continuous telemetry and surface 12 electrocardiograms throughout hospitalization. Results: We observed postoperative atrial fibrillation (AF) in 32 patients (38%, 64.9±10.2 years); of whom 87.5% ( 28 patients) were men. Patients with POAF had significantly larger left atrium (LA) area (18.9 ± 3.7 vs. 21.3 ± 4.9 cm2, p=0.016 ), higher LAAI (10.4 ± 2.0 vs. 12.0 ± 2.6 cm2/m2, p= 0.001), and higher systolic pulmonary artery pressure (30 (2-37) vs. 33 (20-64), p=0.05). In addition, lateral wall Em (9 (3-14) vs. 7 (3-15), p= 0.047), Am (10.8 ± 2.6 vs. 8.3 ± 3.0, p=0.05), and left ventricular ejection fraction (LVEF) (60.5 (23- 78.50) vs. 57.15 (33.10-74.90), p=0.05) were significantly lower in patients with POAF. Based on the backward stepwise model of multivariate analysis, LAAI (p=0.007, 95% CI for OR:1.374 (1.092-1.729)) and LVEF (p=0.039, 95% CI for OR:0.889 (0.796-0.994)) were found to be the strongest independent predictors of POAF. Conclusion: In this study, LAAI and LVEF were independent predictors of POAF development after off-pump CABG surgery. These predictors may be helpful in risk assessment for the possibility of POAF in patients undergoing off-pump CABG surgery.